Analisis wacana pelecehan seksual terhadap pekerja perempuan pada situs never okay project - Setiawan, Dede; Farida, Farida (Soetomo Communication and Humanities, 2020)
Community life in Indonesia is still very much attached to patriarchal culture, where women are positioned as subordinates under the authority of men and stereotypes that negatively label women. Until finally causing social irregularities in the form of cases of sexual harassment against women at work. Utilizing digital media, Never Okay tries to empower women by calling for justice towards assault and harassment of women. With the discourse developed in an article on the story of the disease, this research focuses on how women are depicted in each article posted on the site neverokayproject.org. Utilizing qualitative studies using Norman Fairclough's critical discourse analysis method in unpacking the ideology behind the writing, researchers can conclude that by structuring the discourse in such a way that the article is deliberately made to influence the reader's opinion, especially supporters of the feminine movement.Keywords:Â patriarchy, sexual harassment, never okay, feminism.